Medicion de calidad en semillas de Andropogon gayanus - Sánchez, M.; Ferguson, John E. (1986)
Andropogon gayanus is a species newly introduced and released in five countries of Latin America. Today important comercial seed volumes are being produced and marketed thus developing a need for better knowledge of seed quality standards. Each spikelet pair is composed of a pedicelled spikelet and a sessile spikclet, both presenting pubescence and awns. It is rather difficult also, to determine visually the spikelets beaning a caryopsis. These two characteristics make the seed purity analysis a difficult operation. Two alternative concepts for pure seed definition are described. The first one is known as Modified or lrish which acepts the normal spikelet, with or without a caryopsis, as pure seed; the second concept, known as International , include as pure seed only spikelets containing a caryopsis. This paper presents an alternative methodology called Adjusted Pure Seed (APS). To determine APS, three steps are necessary: a) In a 10g working sample, separate sessile spikelcts, other plant materials and other seeds. b) Estimate the numher of Filled spikelets , in other words, the proportion of sessile spikelets bearing a caryopsis in a 300 sessile spikelets subsample obtained at random. c) Finaily, calculations are made for (i) APS based on modified pure seed times filled spikclets in weight divided by 100; (ii) adjusted inert matter starting from 100 less APS and less other seeds. Proposal is made to determine germination according to the lnternational concept but using sessile spikelets at random and then measuring adjusted germination through a link with Filled Spikelets in number. Brief descriptions are made on techniques for determing seed viability with tetrazolium, moisture content and combined quality indexes. Finally, an exercise is presented to demonstrate the way to calculate the different quality components values, based upon the alternatives modified and adjusted . This paper aims to promote a technical discussion related to the utilization of these alternatives.